Trends and Challenges for Technological Innovation in the Construction Industry: A Systematic Literature Review - Cano Condori, Harold Gaspar (LACCEI, 2025)
Despite the importance of the construction industry, the development and implementation of new technologies within it is the lowest among all industries. This literature review aims to identify the trends and challenges of technological innovation over the past five years. Articles were selected from SCOPUS, IEEE Xplore, and ScienceDirect, and the research was filtered based on the PRISMA methodology. The most studied technologies were artificial intelligence, the use of robots in construction, and BIM. The field with the most applications was sustainable construction. Among the main challenges are the need for further research and the difficulties in adapting technological approaches to practical realities.